Sosialisasi Pengenalan English For Elementary bagi Anak-Anak Kelas 5 & 6 Madrasah Ibtidaiyah Ihya Ulumiddin Banjarmasin - M. Arbain; Erwan Yusuf (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
Mastery of English is crucial in the era of globalization, and English language learning should begin early in elementary school. This community service program aims to improve the understanding and English skills of 5th and 6th grade students at MI Ihya Ulumiddin Banjarmasin through a fun and interactive approach. The methods applied include interactive lectures, question and answer sessions, as well as the use of visual aids and English learning applications. The program also involves pretests and posttests to measure students' understanding before and after the program. The results show a significant improvement in students' understanding and English skills. Most students, who initially had low comprehension, demonstrated positive progress, especially in vocabulary and pronunciation. This program successfully increased students' interest, engagement, and confidence in speaking English. The activity-based approach proved effective in supporting more engaging and developmentally appropriate learning. Moving forward, it is important to continue developing teaching methods that align with students' characteristics to enhance their mastery of English.